TECHNOLOGIES FOR THE DEVELOPMENT OF CREATIVITY OF STUDENTS OF HIGHER EDUCATION ORGANIZATIONS - Usmonova Xurshida Aybekovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article considers the consideration of pedagogical opportunities for the development of creativity of students of higher education organizations - as a factor ensuring the mental maturation of their students. It is also indicated that in the process of higher education institution and further professional development, students must be aware of the content of scientific approaches, concepts, theories, the latest information in their subject. Kryeativ specialists are one of the main tasks of the educational system of rіvoϳlantіrіsh modern ϳamіyat. Therefore ushun today’s educationіarayonіda kryeative teaching, an unusual yyeshim narrowing period requirement in relation to any situation.